PERANAN MODAL SOSIAL PADA MGMP PPKn DALAM MEMBENTUK KOMPETENSI GURU DI KOTA PEKANBARU - Ahmad Eddison; Hambali Hambali; Hariyanti Hariyanti (Bhineka Tunggal Ika: Kajian Teori dan Praktik Pendidikan PKn, 2021)
ABSTRACTThis paper analyzes social capital as an important factor for teachers who are gathered in the MGMP (Musyawarah Guru Mata Pelajaran) organization in the formation of teacher competencies which include; pedagogic competence, personality competence, social competence and professional competence. The purpose of this study is to analyze; 1) social capital and 2) the role of social capital in MGMP-PPKn SMA to form teacher competence in Pekanbaru City. The subjects in this study were administrators and members of the PPKn MGMP, the determination of research subjects (informants) was carried out by purposive sampling technique. Data collection techniques using interviews, observation and documentation. Data analysis techniques through 1) Data Collection 2) Data Reduction 3) Data display, and 4) Data verification. The findings in this study are that the application of social capital in organizations is carried out with three main elements as pillars of togetherness, namely; 1) trust, 2) norms and 3) network. In this study, it does not claim that educator certificates are proof of teacher competence based on policies/laws. However, to get MGMP members to achieve teacher certificates, the findings of this study are that "social capital" has become a part of growing and being maintained and socialized in their togetherness, in other words the social capital in the MGMP organization has played a major role in bringing teachers to achievement, careers and positions in the world of education as a manifestation of the formation of teacher competence itself.Keywords: Social Capital, Teacher Competencies, MGMP, Civic EducationABSTRAKTulisan ini menganalisis modal sosial sebagai faktor penting bagi guru yang terhimpun dalam organisasi MGMP (Musyawarah Guru Mata Pelajaran) dalam pembentukan kompetensi guru yang meliputi; kompetensi pedagogik, kompetensi kepribadian, kompetensi sosial dan kompetensi profesional. Tujuan penelitian ini adalah untuk menganalisis; 1) modal sosial dan 2) peran modal sosial dalam MGMP-PPKn SMA membentuk kompetensi Guru di Kota Pekanbaru. Subjek dalam penelitian ini ialah pengurus dan anggota MGMP PPKn, penentuan subjek penelitian (informan) dilakukan dengan teknik purposive sampling. Teknik pengumpulan data menggunakan metode wawancara, observasi dan dokumentasi. Teknik analisis data melalui 1) Pengumpulan Data 2) Reduksi Data 3) Display data, dan 4) Verifikasi data. Temuan dalam penelitian ini bahwa penerapan modal sosial pada organisasi dilakukan dengan tiga unsur utama sebagai pilar kebersamaan yaitu; 1) kepercayaan, 2) norma dan 3) jaringan. Dalam penelitian ini sama sekali tidak mengklaim bahwa sertifikat pendidik adalah pembuktian kompetensi guru berdasarkan kebijakan/UU. Namun, untuk sampai anggota MGMP meraih sertifikat guru, maka temuan penelitian ini bahwa ”modal sosial” telah menjadi bagian tumbuh dan terjaga serta tersosialisasi dalam kebersamaan mereka, dengan kata lain modal sosial yang ada dalam organisasi MGMP menjadi andil besar telah mengantarkan guru ke prestasi, karier dan jabatan dalam dunia pendidikan sebagai manifestasi dari terbentuknya kompetensi guru itu sendiri.Kata Kunci: Modal Sosial, Kompetensi Guru, MGMP, PPKn